Is being right legitimate? Addressing public outcries on social media. (March 2021) - Holmgreen, Lise-Lotte
Abstract: With social media, organisations have had to face new realities in their exposure to public condemnation. Thus, social media provide publics with instant access to voicing disapproval of organizational behaviour, potentially leading to long-term negative effects on organizational image and earnings (Holmgreen 2015). This realisation forms the background of the article which discusses the clash between organisational legitimisation strategies, which seek to justify actions through reference to their just and appropriate character, and the public evaluation of the very same conduct as inappropriate and immoral (Bréton and Coté 2006; Suchman 1995). Drawing on a critical discourse approach to legitimation (Fairclough 2003; Van Leeuwen 2008) and a corpus of press releases and public social media comments, the article analyses the case of a Danish steakhouse chain whose legal actions against a smaller restaurant owner spurred a public outcry and firestorm on social media, leading to the chain's imminent closure four years later. The analysis reveals two distinctly different discourses that reflect basic social and cultural values, on the one hand, and business values, on the other. Thus, the analysis suggests that despite the existence of a shared social system based on the rule of law, organizational and public (legitimation) strategies may follow apparently irreconcilable paths that challenge the very foundation of business.